Measuring blood glucose before or after lumbar puncture - Shi, Kaili; Li, Xue; Li, Ying; Tan, Xiaohua; Zheng, Kelu; Chen, Wenxiong; Li, Xiaojing (PeerJ, 2023)
Background The ratio of cerebrospinal fluid (CSF) to peripheral blood glucose at the same period is an important index for diagnosing and monitoring the efficacy of central nervous system infection, especially bacterial meningitis. Some guidelines refer that blood glucose measurement should be carried out before lumbar puncture. The main reason is to avoid possible effect of stress response induced by lumbar puncture on the level of blood glucose. However, there is no consensus on whether it should be followed in actual clinical work, since up to now no research work having been published on whether lumbar puncture will induce the changes on blood glucose. Our study aimed to investigate the changes of peripheral blood glucose before and after lumbar puncture. Methods In order to clarify the influence of timing of peripheral blood glucose measurement at the same period of lumbar puncture, a prospective study was conducted including children with an age range from 2 months to 12 years old in the neurology department of a medical center. For those children who need lumbar puncture due to their illness, their blood glucose was measured within 5 min before and after lumbar puncture, respectively. The blood glucose level and the ratio of CSF to blood glucose before and after lumbar puncture were compared. Meanwhile, the patients were divided into different groups according to the factors of sex, age and sedation or not for further comparison. All statistical analyses of the data were performed using SPSS version 26.0 for Windows. Results In total, 101 children who needed lumbar puncture during hospitalization from January 1, 2021, to October 1, 2021, were recruited with 65 male and 36 female respectively. There was no significant difference on the level of blood glucose, CSF to blood glucose ratio before and after lumbar puncture among the children (p > 0.05). No differences were observed within different groups (sex, age, sedation or not) either. Conclusion It is unnecessary to emphasize blood glucose measurement should be carried out before lumbar puncture, especially for pediatric patients. From the perspective of facilitating smoother cerebrospinal fluid puncture in children, blood glucose measurement after lumbar puncture might be a better choice.
Keywords: Lumbar puncture; Blood glucose; Cerebrospinal fluid glucose; CSF glucose